Carbon deficit checks in high resolution and compensation under regional inequity. (15th February 2023) - Xia, Mengyao; Chuai, Xiaowei; Xu, Hongbo; Cai, Helen Huifen; Xiang, Ai; Lu, Junyu; Zhang, Fengtai; Li, Mengying
Abstract: Carbon compensation is an effective way of reducing carbon emissions. However, previous studies in this field have been limited and have not examined high-precision scientific carbon compensation under regional inequity. The present study examined initial carbon compensation in the grid and developed a new equitable carbon compensation model. Additionally, it modified the carbon compensation value for each province and analysed how land-use change affected carbon compensation. The results show that, after the modification, the entire carbon deficit reached 17.34 × 10 8 t C in 2015, representing a decrease of 14% compared with the initial carbon deficit. The area with negative carbon deficit values accounted for 36% of the whole area, concentrated mainly in the south, southwest and northwest. Without modification, the initial carbon compensation reached 537 × 10 8 USD, and only Yunnan, Sichuan and Hainan provinces being eligible to receive compensation. The final modified carbon compensation was approximately 20% of the initial values, and 11 provinces were eligible to obtain compensation. The other provinces responsible for paying the carbon compensation costs were typically concentrated in Central and Eastern China. Land-use changes in 2015 led to increases in the initial carbon compensation and modified carbon compensation of 3.74 × 10 8 and 0.13 × 10 8 USD, respectively. The per-unit land-use change caused greater increases in carbon emissions in China's big cities and the provinces in Central and East China. Some policies, such as macro-control by the central government, diversified forms and patterns of compensation, and auxiliary measures should be formulated/proposed. Highlights: Carbon deficit and compensation were checked under regional equity. Both domestic trade and regional interior differences were used to evaluate the equity. The developed regions usually benefit more and should pay for carbon compensation.